Нові надходження предметів кола східноєвропейських виїмчастих емалей у Сумському обласному краєзнавчому музеї (попереднє повідомлення) - Білинська, Л.І.; Білик, В.М.; Бугай, О.М.; Гопкало, О.В.; Гороховський, Є.Л.; Деревянко, О.М. (Археологія і давня історія України, 2021)
Опубліковано предмети з виїмчастими емалями, передані для зберігання в Сумський обласний краєзнавчий музей мешканцями міста
Суми — С. І. Гуцаном та Р. А. Бобковим протягом
2012—2020 рр. Серед них фібули (підковоподібні,
трикутні, броші), підвіски (хрестоподібні, лунниці), ланцюги, браслети, очілля, гривни, накладки,
персні, трапецієподібні підвіски, остроги та ін.
Більшість із них належать до другого етапу розвитку емалевих прикрас, за Є. Л. Гороховським.
Метал та емалеві вставки речей проаналізовано
співробітниками Інституту прикладної фізики
НАН України за допомогою рентгенофлуоресцентного спектрометра. During 2018—2020 items with Champleve enamels
were presented to Sumy Regional Museum by Sumy
residents, S. I. Gutsan and R. A. Bobkov. They were
shown at an exhibition dedicated to the 100th anniversary
of the Museum in September 2020. The collection consists of more than 70 items (tabl. 1). There are
brooches (horseshoe-shaped, triangular, round), pendants
(cruciform, lunnula), chains, bracelets, diadems,
torques, appliquй, finger-rings, trapezoidal pendants,
spurs etc. Because these finds were kept in private collections
and were presented to the Museum by their
owners, the items could be considered accidental finds
except location of them was more or less accurate.
Preliminary analysis of things from the collection allowed
us to determine the following. The area of finds
includes different areas of Sumy region, but those found
in Sumy’s suburbs significantly dominate, and by dating
they mostly belong to the second stage of development
of East European Champleve enamels, according
to E. Gorokhovskyi — to the middle and second half of
3rd century. Metal and enamel of things were analyzed
by the researchers of The Institute of Applied Physics
of NASU using an X-ray fluorescence spectrometer.
Situation around archeological monuments requires
a rapid reconstruction, adaptation of science to new
unfavorable conditions. This publication is prompted
by an attempt to obtain maximum information from
sources whose reliability is questionable. Moreover,
the things analyzed in this publication are of great
importance for solving many important questions of
archeology, in particular, for the reconstruction of the
Slavonic peoples’s genesis.